2011
DOI: 10.5053/ejobios.2011.5.0.4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the growth parameters of legumes grown in fipronil-stressed soils

Abstract: For the first time, genetic variability and differentiation among five annual caraway (Carum carvi) populations originating from Tunisia, Germany and Egypt were examined. Random Amplified Polymorphic DNA (RAPD) marker data were obtained and analysed with respect to genetic diversity, population structure and gene flow. Fourteen primers generated a total of 136 discernible and reproducible bands across the analyzed populations, out of which 56 were polymorphic. The UPGMA cluster analysis permitted the discrimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Legumes are important in nitrogen fixation in soils and have increasingly become models/markers of toxic effects of chemicals (such as pesticides) in the environment, on plants. Ahemad and Khan [23] reported that fipronil (an insecticide) was stressful to legumes including chickpea, pea, lentil, and green gram, and observed the negative effects of the insecticide on shoot dry biomass, chlorophyll content, root nodule numbers and biomass. Chlorpyriphos had a significantly lower root nodule number/plant than Ridomil.…”
Section: Discussionmentioning
confidence: 99%
“…Legumes are important in nitrogen fixation in soils and have increasingly become models/markers of toxic effects of chemicals (such as pesticides) in the environment, on plants. Ahemad and Khan [23] reported that fipronil (an insecticide) was stressful to legumes including chickpea, pea, lentil, and green gram, and observed the negative effects of the insecticide on shoot dry biomass, chlorophyll content, root nodule numbers and biomass. Chlorpyriphos had a significantly lower root nodule number/plant than Ridomil.…”
Section: Discussionmentioning
confidence: 99%